Health-related quality of life in breast cancer patients in Asia: A meta-analysis and systematic review - Chen, Xinyu; Wu, Chenxi; Bai, Dingxi; Gao, Jing; Hou, Chaoming; Chen, Tingting; Zhang, Lulu; Luo, Huan (Frontiers in Oncology, 2022)
Objectives: The primary purpose of this meta-analysis and systematic review is to evaluate the health-related quality of life (HRQoL) of Asian breast cancer (BC) patients to understand their holistic HRQoL level and provide medical and nursing recommendations to improve and preserve their quality of life. Methods: A comprehensive literature search was conducted to find cross-sectional studies published in Chinese and English concerning health-related quality of life in BC patients from inception to March 14, 2022. The databases consulted included PubMed, Web of Science, Embase, Cochrane, Psyclnfo, CINAHL and CNKI. Literature screening, data extraction, risk bias assessment and data synthesis were independently carried out by two researchers. The software programs Endnote X9 and Stata 15.0 were used during the meta-analysis process. Results: Out of 8,563 identified studies, 23 cross-sectional studies involving 3,839 Asian BC patients were included in this meta-analysis. Two tools – namely EORTC QLQ-C30 and EORTC QLQ-BR23 – were employed to evaluate the HRQoL of BC patients in Asia. The pooled mean of the global health status of Asian BC patients was 58.34 (95% confidence interval [CI]: 53.66-63.02). According to functional subscales of EORTC QLQ-C30 and EORTC QLQ-BR23, Asian BC patients suffered from the worst emotional functioning (pooled mean=66.38; 95% CI: 59.66-73.11) and sexual enjoyment (pooled mean=49.31, 95% CI: 31.97-63.36). In addition, fatigue (pooled mean=42.17, 95% CI: 34.46-49.88) and upset by hair loss (pooled mean=48.38, 95% CI: 36.64-60.12) were the most obvious symptoms that Asian BC patients were experiencing according to the meta-analysis results of the EORTC QLQ-C30 and EORTC QLQ-BR23 symptoms’ subscales. Conclusion: Asian BC patients enjoy a relatively low health-related quality of life due to their prominent decline in body functions and awful experiences caused by obvious symptoms. It is suggested that timely, appropriate, and targeted intervention should be provided in relation to physical, psychological and social aspects to enhance these patients’ functions and relieve them of adverse symptoms, to improve their overall health-related quality of life. Keywords: Asia, breast cancer, health-related quality of life, meta-analysis.